Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Perawat Dalam Penerapan Operan Shift Dengan Metode Sbar Di Ruang Rawat Inap RSIA Bunda Sejahtera Kotabumi Tangerang - Widhawati, Riswahyuni; Purwanti, Heni; Nawawi, Nawawi (STIKes IMC Bintaro, 2023)
ABSTRACT Introduction: Hypertension can be prevented and controlled by cultivating healthy living behaviors. Healthy living behaviors include consuming foods with balanced nutrition that meet nutritional needs with elements rich in fiber, low in fat and low in sodium (less than 6 grams of sodium per day), exercising regularly, getting enough rest, positive thinking, not smoking, and not smoking. consuming alcohol because smoking and alcohol can increase the risk of hypertension. However, the lack of adequate public knowledge about hypertension and its prevention tends to increase the incidence of hypertension. Research objective: to determine the relationship between knowledge and attitudes of the elderly towards hypertension diet in elderly patients aged 60-74 years at Mitra Husada Hospital Tangerang in 2022. The form of research used is descriptive analytic with a cross sectional approach. Sampling in this study using a non-probability sampling technique with a purposive sampling approach that is based on certain considerations made by the researcher himself based on the characteristics or characteristics of the population that have been known previously. The instrument used is a questionnaire, while the statistical test uses the Chi Square test. The results of the study: showed that there was a relationship between knowledge and the attitude of the elderly towards hypertension diet in elderly patients aged 60-74 years at Mitra Husada Hospital Tangerang in 2022 with statistical test results, namely P Value 0.001. Suggestion: it is hoped that this research can be an experience, can become knowledge and can motivate to continue to do good things in order to increase insight and knowledge of elderly people with hypertension and to their families in an effort to regulate the right diet and lifestyle in order to prevent the recurrence of hypertension.